2020
DOI: 10.1074/jbc.ra120.014738
|View full text |Cite
|
Sign up to set email alerts
|

A seven-residue deletion in PrP leads to generation of a spontaneous prion formed from C-terminal C1 fragment of PrP

Abstract: Prions result from a drastic conformational change of the host-encoded cellular prion protein (PrP), leading to the formation of beta-sheet-rich, insoluble and protease-resistant self-replicating assemblies (PrPSc). The cellular and molecular mechanisms involved in spontaneous prion formation in sporadic and inherited human prion diseases or equivalent animal diseases are poorly understood, in part because cell models of spontaneously-forming prions are currently lacking. Here, extending studies on the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Recently, we showed that the alpha-cleaved C1-fragments from PrP C (truncation at amino acids 113/115, [67]) were convertible into prions in RK13 cells, when part of the a-helix H2 was deleted [68]. This result and the infectivity of LMW PrP Sc fragments stand in apparent contradiction with several reports suggesting that PrP amino acids ~90-100 to 155, notably the central polybasic domain with 4 lysines at aa ~100-110, are an obligate domain of PrP res infectious core [18,[69][70][71].…”
Section: An Infectious N-terminally Truncated Mini-prionmentioning
confidence: 99%
“…Recently, we showed that the alpha-cleaved C1-fragments from PrP C (truncation at amino acids 113/115, [67]) were convertible into prions in RK13 cells, when part of the a-helix H2 was deleted [68]. This result and the infectivity of LMW PrP Sc fragments stand in apparent contradiction with several reports suggesting that PrP amino acids ~90-100 to 155, notably the central polybasic domain with 4 lysines at aa ~100-110, are an obligate domain of PrP res infectious core [18,[69][70][71].…”
Section: An Infectious N-terminally Truncated Mini-prionmentioning
confidence: 99%
“…Although the regulatory role for C1 fragment production is unresolved, it seems that it negatively modulates key steps of PrP conversion process, namely, misfolding, replication, and fibrillization ( Westergard et al, 2011 ; Campbell et al, 2013 ). Nevertheless, under experimental conditions, C1 lacking the C-terminal portion of H 2 can be converted into a C1 prion by full-length spontaneous prion harboring the same deletion ( Munoz-Montesino et al, 2020 ). Regarding C2 fragment, data strongly suggest that its accumulation would be a key product of the PrP C processing in prion replication ( Dron et al, 2010 ).…”
Section: Structure Processing and Function Of Prpmentioning
confidence: 99%
“…This raises the possibility that PrP C cleavage may modulate prion diseases by reducing the amount of full-length PrP C available for conversion or C1 fragment-mediated inhibition of full-length PrP C conversion. Interestingly, a laboratory-generated PrP C deletion mutant was found to undergo spontaneous conversion to a prion of similar size as the C1 fragment [ 13 ]. This new type of prion was also able to infect and propagate in a cell line that expressed the deletion-mutant PrP C C1 fragment only.…”
Section: Introductionmentioning
confidence: 99%